2012
DOI: 10.1074/jbc.m112.374751
|View full text |Cite
|
Sign up to set email alerts
|

Prenyltransferases Regulate CD20 Protein Levels and Influence Anti-CD20 Monoclonal Antibody-mediated Activation of Complement-dependent Cytotoxicity

Abstract: Background:The influence of farnesyltransferase inhibitors (FTIs) on CD20 levels is unknown. Results: FTIs increase CD20 expression and improve rituximab-mediated activation of complement-dependent cytotoxicity. Conclusion: FTIs sensitize tumor cells to anti-CD20 mAbs. Significance: The combination of FTIs with anti-CD20 mAbs seems to be a reasonable therapeutic approach worth to be tested in patients with B-cell tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Previous reports demonstrated that GEM also activated NF‐ k B in pancreatic cancer cells . The CD20 gene promoter contains binding sites to Sp1, NF‐ k B, Oct and PU.1 . Based on these findings, we presume that GEM‐activated NF‐ k B binds to the CD20 promoter to induce CD20 transcriptional activation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous reports demonstrated that GEM also activated NF‐ k B in pancreatic cancer cells . The CD20 gene promoter contains binding sites to Sp1, NF‐ k B, Oct and PU.1 . Based on these findings, we presume that GEM‐activated NF‐ k B binds to the CD20 promoter to induce CD20 transcriptional activation.…”
Section: Discussionsupporting
confidence: 56%
“…Some therapeutic agents, such as farnesyltransferase inhibitors, bryostatin‐1, histone deacetylase inhibitors and some cytokines, can enhance CD20 expression in lymphoma, and upregulation of CD20 expression on B cell lymphoma cells increases the cytotoxic activity of rituximab . In the present study, we demonstrate that gemcitabine (GEM), which is conventionally used for DLBCL treatment, augments CD20 expression on DLBCL cells.…”
supporting
confidence: 50%
“…Furthermore, CD20 expression is highly variable and rather low on the cells of chronic lymphocytic leukemia (CLL) when compared to other B-cell malignancies or healthy B cells [3]. Notably, some experimental approaches to pharmacologically modulate CD20 expression levels were proposed, nevertheless, none of the strategies has ever been transferred into the clinical use [4,5]. So far, it is impossible to predict CD20 expression changes, as the precise molecular mechanisms of CD20 regulation and its biological function remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid rafts are specialized microdomains of the plasma membrane that are enriched in sphingolipid and cholesterol, and play an important role in the initiation of many anticancer drug-induced signaling pathways and toxicological effects. Anticancer drugs are able to suppress cell growth and induce apoptosis of tumor cells through disrupting lipid raft integrity [32,47]. The redistribution of CD-20 may result in lipid raft disruption, activate or deactivate raft-associated proteins, such as death receptors and protein kinases in apoptotic pathway which are correlated with efficiency of complementdependent cytotoxicity and antibody-dependent cellmediated cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%